The Role of the Madrasah Head in Implementing the Independent Curriculum at the Madrasah - Nurhayati; Pebri Edy (AMUYA: JOURNAL OF MANAGEMENT, 2025)
The aim of this policy paper is to find out the role of the Madrasah Head in implementing the Merdeka Curriculum. The research method used is a qualitative, qualitative is a series of procedures designed to produce descriptive data in written or spoken words. The kinds of research are descriptive, that describes about phenomena, events and incidents in certain groups. The results show that; As Madrasah leaders must work together with educators and education staff to improve the quality of education in Madrasah. The role of the madrasa head in implementing the Curriculum merdeka is to encourage a student-centered learning process and allow flexibility for educators and their education staff. In solving problems related to the Problems of implementing the Merdeka Curriculum in Madrasas, the Head of the Madrasah has an active role to answer current problems, related to the implementation of the Merdeka Curriculum effectively and efficiently.